Novel molecular genetic defects and immunopathological mechanisms in Brazilian patients with mycobacterial diseases. - Khan, Taj Ali (2014)
We aimed to characterize well-know PIDs, novel genetic defects and immunopathological mechanisms in Brazilian patients with susceptibility to mycobacterial diseases. The patients developed different mycobacterial diseases and M. tuberculosis was the most frequent species. Molecular and genetic analysis revealed mutations in different genes: RAG1 (P1), CD40LG (P2, P3, P4), NEMO (P5), NCF1 (P6), TLR2 (P7) IL-12Rb2 (P8), IL-12Rb1 (P9), TLR10 (P10), DKC1(P11), SOCS-1(P12) and IRAK2 (P13). Finally, MDMs from patients phagocytose normally but were unable to appropriately control intracellular M. tuberculosis growth in comparison to MDMs from healthy subjects. We concluded that the Brazilian patients have heterogeneous mutations previously associated with susceptibility to mycobacterial diseases and novel genetic variations were identified suggesting novel PIDs. In addition, the inability of MDMs to control the intracellular growth of M. tuberculosis indicates this contributes to patients´ susceptibility to mycobacterial infections.